Developing a technological pedagogical content knowledge (TPACK) assessment for preservice teachers learning to teach English as a foreign language - Baser, Derya; Kopcha, Theodore J.; Ozden, M. Yasar (Routledge Journals, Taylor & Francis Ltd, 2016)
This paper reports the development and validation process of a self-assessment survey that examines technological pedagogical content knowledge (TPACK) among preservice teachers learning to teach English as a foreign language (EFL). The survey, called TPACK-EFL, aims to provide an assessment tool for preservice foreign language teachers that addresses subject-specific pedagogies and technologies. Using mixed methods approach, survey items were generated first using qualitative methods (e.g. expert interviews and document analysis). The content validity of the items was established through expert and preservice teacher reviews. The survey was then validated through two rounds of exploratory factor analysis (EFA), the first with 174 preservice EFL teachers and the second with 204 preservice EFL teachers. The results of the first round indicated a five-factor structure: technological knowledge (TK), content knowledge (CK), pedagogical knowledge (PK), pedagogical content knowledge (PCK) and a fifth factor that combined TCK, TPK, and TPACK items. After revising the survey, the second round of EFA results showed a seven-factor structure that was consistent with the TPACK framework. The final TPACK-EFL survey included a total of 39 items: 9 TK, 5 CK, 6 PK, 5 PCK, 3 TCK, 7 TPK, and 4 TPACK. The results offer survey developers and teacher educators insight into establishing clear boundaries between the TPACK constructs. In particular, subject-specific strategies were used to generate clear and distinct items within the TCK and TPK constructs. Implications for developing other subject-specific TPACK surveys and using the TPACK-EFL survey in other countries are discussed.
Keywords: English as a foreign language; technology integration; technological pedagogical content knowledge; teacher education; assessment